Spectral kinetic characteristics of Li,Bi-activated cadmium tungstate crystals; Journal of Applied Spectroscopy; Vol. 80, iss. 3 - Lisitsyn V. M. Viktor Mikhailovich; Valiev D. T. Damir Talgatovich; Tupitsyna I. A.; Polisadova E. F. Elena Fyodorovna; Oleshko V. I. Vladimir Ivanovich (2013, 2013)
Title screen